Pharmaceutical services in a Mexican pain relief and palliative care institute - Escutia Gutierrez R; Cortéz Alvarez CR; Álvarez Alvarez RM; Flores Hernandez JL; Gutiérrez Godinez J; López y Lopez JG (Centro de Investigaciones y Publicaciones Farmaceuticas, 2007)
Neither the purchase nor the distribution of pharmaceuticals in hospitals and community pharmacies in Mexico is under the care of pharmacists. Some are under control of physicians.This report presents the results of the implementation of somef pharmaceutical services for the Jalisco Pain Relief, and Palliative Care Institute (Palia Institute), under the direction of the Secretary of Health, Government of Jalisco. The services implemented were drug distribution system, Drug Information Service, Pharmacovigilance Program , and home pharmacotherapy follow-up pilot program for patients with advanced illness, with the ultimate using the appropriate medication. The drug distribution system included dispensing of opioid pain medications, antidepressants, anticonvulsants, NSAIDs, anxiolytic drugs, steroid drugs, laxatives, and anti-emetics. The frequently used drugs were morphine sulfate (62%), amitriptyline (6.4%), and dextropropoxyphene (5.8%). The Drug Information Service answered 114 consultations, mainly asked by a physician (71%) concerned with adverse drug reactions and contraindications (21%). The pharmacovigilance program identified 146 suspected adverse drug reactions and classified them reasonably as possible (27%), probable (69%), and certain (4%). These were attributed mainly to pregabalin and tramadol. The home pharmacotherapy follow-up pilot program cared patients with different cancer diagnoses and drug-related problems (DRP), which were identified and classified (according to second Granada Consensus) for pharmaceutical intervention as DRP 1 (5%), DRP 2 (10%), DRP 3 (14%), DRP 4 (19%), DRP 5 (24%), or DRP 6 (28%). This report provides information concerning the accurate use of medication and, above all, an opportunity for Mexican pharmacists to become an part of health teams seeking to resolve drug-related problems.